2022
DOI: 10.1152/ajprenal.00461.2021
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of kidney mitochondrial function by caloric restriction

Abstract: Caloric restriction (CR) prevents obesity and increases resilience against pathological stimuli in laboratory rodents. At the mitochondrial level, protection promoted by CR in the brain and liver is related to higher calcium uptake rates and capacities, avoiding Ca2+-induced mitochondrial permeability transition. Dietary restriction has also been shown to increase kidney resistance against damaging stimuli, but if these effects are related to similar mitochondrial adaptations has not been uncovered. Here, we c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Autophagy is mainly activated in response to decreased nutrient availability 17 . Interestingly, works published by our group have shown that mitochondrial Ca 2+ transport is strongly regulated by nutritional interventions such as caloric restriction, which is also well known to promote autophagy 30,40,41 . As a starting point to understand the interplay between mitochondrial Ca 2+ transport and autophagy, we investigated whether NCLX levels are sensitive to calorie restriction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy is mainly activated in response to decreased nutrient availability 17 . Interestingly, works published by our group have shown that mitochondrial Ca 2+ transport is strongly regulated by nutritional interventions such as caloric restriction, which is also well known to promote autophagy 30,40,41 . As a starting point to understand the interplay between mitochondrial Ca 2+ transport and autophagy, we investigated whether NCLX levels are sensitive to calorie restriction.…”
Section: Resultsmentioning
confidence: 99%
“…17 Interestingly, works published by our group have shown that mitochondrial Ca 2+ transport is strongly regulated by nutritional interventions such as caloric restriction, which is also well known to promote autophagy. 30,40,41 As a starting point to understand the interplay between mitochondrial Ca 2+ transport and autophagy, we investigated whether NCLX levels are sensitive to calorie restriction. We consistently observed that mitochondria isolated from the livers of mice that underwent 4 months of caloric restriction contained higher levels of NCLX protein than animals on an ad libitum diet (Figure 1A).…”
Section: Nclx Expression Is Increased By Nutrient Restrictionmentioning
confidence: 99%
“…Autophagy is mainly activated in response to decreased nutrient availability (Lahiri et al, 2019). Interestingly, works published by our group have shown that mitochondrial Ca 2+ transport is strongly regulated by nutritional interventions such as caloric restriction, which is also well known to promote autophagy (Menezes-Filho et al, 2017; Amigo et al, 2017; Serna et al, 2022). As a starting point to understand the interplay between mitochondrial Ca 2+ transport and autophagy, we investigated whether NCLX levels are sensitive to calorie restriction.…”
Section: Resultsmentioning
confidence: 99%
“…After the diet period, mitochondria were isolated from the livers of mice as described previously (Serna et al, 2022). Briefly, the livers were minced, washed repeatedly with ice-cold PBS and suspended in isolation buffer (250 mM sucrose, 10 mM HEPES, 1 mM EGTA, 1 mM EDTA, 1 mg/ml BSA fatty acid-free).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, this NA-STZ diabetes animal model may also be used to evaluate any potential renoprotective effects of caloric restriction [ 142 , 143 , 144 ], intermittent caloric restriction [ 145 , 146 ], exercise [ 147 , 148 , 149 , 150 ], and ketone bodies [ 151 , 152 , 153 , 154 ], which all have been demonstrated to provide beneficial effects on the kidney in a variety of pathological conditions [ 155 , 156 ]. Indeed, the underlying mechanisms of renoprotection conferred by these approaches in this non-obese type 2 diabetes model remain to be comprehensively elucidated.…”
Section: Redox-related Mechanisms That Remain To Be Elucidated In Thi...mentioning
confidence: 99%